High-color-fastness structural color film and preparation method thereof

Through the assembly of modified nanocolloid microspheres and carbon black, combined with the combination of modified polyurethane precursor and opal photonic crystal, the color fastness problem of structural color film under external force is solved, and high color fastness and stability are achieved Preparation of structural color films.

CN119119531AInactive Publication Date: 2024-12-13ANHUI YISHANG TEXTILE TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411303959.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing structural color films are easily destroyed under the action of external forces, resulting in low color fastness and difficulty in maintaining color rendering ability.

Method used

Modified nanocolloidal microspheres and carbon black are used as photonic crystal assembly elements, and the crosslinking density is increased through the core crosslinking agent diethylene benzene to form a mesh structure, and the inner and outer layers are connected by covalent bonds, combining with the modified polyurethane precursor Hydrogen bonding with opal photonic crystals enhances structural stability and compatibility, forming a photonic crystal that is soft on the outside and hard on the inside.

Benefits of technology

It improves the stability and color fastness of the structural color film, avoids cracks, keeps the photonic crystal structure from being damaged, has better color development effect, and enhances mechanical properties and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005048552810000081
    Figure BDA0005048552810000081
Patent Text Reader

Abstract

The invention discloses a high-color-fastness structural color film and a preparation method thereof, and belongs to the technical field of structural color films, and the preparation method comprises the following steps: S1, adding modified nano colloidal microspheres and carbon black into absolute ethyl alcohol, and carrying out ultrasonic dispersion for 40 min to obtain a microsphere dispersion liquid; s2, uniformly spreading the microsphere dispersion liquid on a smooth and flat polyfluortetraethylene plate, and drying at 40-45 DEG C to obtain a modified microglobulin photonic crystal template; and S3, injecting the modified polyurethane precursor solution into the modified microglobulin stone photonic crystal template, vacuumizing, defoaming, and curing at 80 DEG C to obtain the high-color-fastness structural membrane. According to the invention, the modified nano colloidal microspheres and the carbon black are taken as assembly elements of the photonic crystal, so that the stability of the structural color film is improved, and meanwhile, under the synergistic effect of the modified polyurethane precursor solution, cracks can be effectively prevented, and the photonic crystal structure is prevented from being damaged, so that the color fastness and durability of the structural color film are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of structural color films, and particularly relates to a high color fastness structural color film and a preparation method thereof. Background Art

[0002] In the field of modern industrial design and materials science, structural color films have attracted widespread attention due to their unique optical properties and environmental attributes. Structural color films are composed of two or more nanoparticles with different refractive indices, which produce colors through the interference, diffraction or scattering of light by physical microstructures. Compared with traditional pigment coloring, structural color films have the advantages of being non-fading, environmentally friendly, and color can be controlled through design.

[0003] In the prior art, structural color films are based on nano-microspheres and use self-assembly technology to construct an ordered photonic crystal structure on the surface of a substrate. However, the photonic crystals constructed by hard nano-microspheres will destroy the crystal structure under the action of external forces, causing irreversible changes in the fragile fine structure, resulting in the structural color film losing its color rendering ability. Therefore, how to produce a structural color film with high color fastness is a technical problem that needs to be solved at present. Summary of the invention

[0004] The object of the present invention is to provide a high color fastness structural color film and a preparation method thereof, so as to solve the problems in the background technology.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing a structural color film with high color fastness comprises the following steps:

[0007] S1, adding modified nano-colloidal microspheres and carbon black into anhydrous ethanol, and ultrasonically dispersing for 40 minutes to obtain a microsphere dispersion;

[0008] S2, evenly spreading the microsphere dispersion on a smooth and flat polytetrafluoroethylene plate, and drying at 40-45° C. to obtain a modified microsphere opal photonic crystal template;

[0009] S3. Injecting the modified polyurethane precursor liquid into the modified microsphere opal photonic crystal template, and then vacuuming and defoaming, and curing at 80° C. to obtain a high color fastness structural film.

[0010] Furthermore, the weight ratio of the anhydrous ethanol, the modified nano-colloidal microspheres and the carbon black is 300-400:80-90:4-6.

[0011] Furthermore, the thickness of the high color fastness structural film is 0.1-0.5 mm.

[0012] Furthermore, the modified nano-colloidal microspheres are prepared by the following steps:

[0013] A1. Add sodium dodecylbenzene sulfonate to deionized water, stir and mix, add styrene in a total amount of 25%-27% and divinylbenzene in a total amount of 7%-20% at 70-80° C., stir and react for 20-30 min, then add a potassium persulfate solution with a concentration of 2wt%, stir and mix, then dropwise add the remaining styrene and the remaining divinylbenzene, control the dropping time to be 30-40 min, after the dropwise addition is completed, stir and react for 1-1.5 h, and then obtain polystyrene colloidal microspheres after rotary evaporation; use sodium dodecylbenzene sulfonate as anionic surfactant, divinylbenzene as internal crosslinking agent, and styrene as core monomer to crosslink to obtain polystyrene seeds, then slowly dropwise add the remaining styrene monomer and divinylbenzene to make the polystyrene seeds grow evenly, and obtain polystyrene colloidal microspheres with good particle size distribution;

[0014] A2. Add polystyrene colloidal microspheres to deionized water, stir to mix, add methyl methacrylate and butyl acrylate dropwise, mix, then add allyl methacrylate dropwise, control the adding time to be 30-40min, after the adding is completed, continue to stir and react for 1-2h, and then obtain modified nano colloidal microspheres after rotary evaporation; use allyl methacrylate as a shell crosslinker, methyl methacrylate and butyl acrylate as shell monomers, covalently bond with the double bonds on the surface of the polystyrene colloidal microspheres, and anchor them on the surface of the polystyrene microsphere particles, to obtain "soft outside and hard inside" modified nano colloidal microspheres with polystyrene as the core and poly (methyl methacrylate-butyl acrylate) as the shell.

[0015] Furthermore, the usage ratio of the deionized water, sodium dodecyl sulfate, styrene, divinylbenzene and potassium persulfate solution is 90 mL: 0.05-0.1 g: 15-20 mL: 0.5-1 mL: 15-18 mL.

[0016] Furthermore, the volume ratio of the deionized water, the polystyrene colloidal microspheres, the methyl methacrylate, the butyl acrylate and the allyl methacrylate is 50:4-5:3-4:5-7.5:0.1-0.25.

[0017] Furthermore, the particle size of the modified nano-colloidal microspheres is 200-300 nm.

[0018] Furthermore, the modified polyurethane precursor solution is prepared by the following steps:

[0019] Add propylene glycol and 2,2-dihydroxymethylbutyric acid to polycarbonate diol, stir and mix at 80-90° C., cool to 60-70° C., add 4,4'-dicyclohexylmethane diisocyanate, stir and mix, cool to 50-55° C., add dibutyltin dilaurate, stir and react for 2-5 minutes to obtain a modified polyurethane precursor liquid; with polycarbonate diol as the main chain, dibutyltin dilaurate as the catalyst, 2,2-dihydroxymethylbutyric acid as the chain extender, and propylene glycol as the cross-linking agent, the polycarbonate diol is polymerized with the hydroxyl group of 2,2-dihydroxymethylbutyric acid and the isocyanate group of 4,4'-dicyclohexylmethane diisocyanate to obtain a modified polyurethane precursor liquid containing carboxyl side chains.

[0020] Furthermore, the usage ratio of the polycarbonate diol, propylene glycol, 2,2-dihydroxymethylbutyric acid, 4,4'-dicyclohexylmethane diisocyanate and dibutyltin dilaurate is 15-20 g: 0.1-0.5 mL: 0.2-0.4 g: 1.5-3 mL: 0.3-0.5 mL.

[0021] A structural color film with high color fastness is prepared by the above preparation method.

[0022] Beneficial effects of the present invention:

[0023] The present invention uses modified nano-colloidal microspheres and carbon black as the assembly primitives of the photonic crystals, and improves the crosslinking density of the polystyrene core through the core crosslinking agent divinylbenzene, so that the original linear structure is transformed into a dense network structure, which not only improves the core hardness of the modified nano-colloidal microspheres, but also effectively prevents the shell monomer from diffusing into the core, so as to form a core with good particle size distribution. At the same time, the surface of the modified nano-colloidal microspheres contains rich ester groups, and the inner and outer layers are connected by covalent bonds, so as to improve the structural stability of the modified nano-colloidal microspheres, and endow the photonic crystal structural color film with the performance of being soft on the outside and hard on the inside. When the photonic crystal structural color film is subjected to external forces, the flexible shell on the surface of the modified nano-colloidal microspheres can disperse the stress, effectively avoid the generation of cracks, thereby improving the stability of the structural color film, and at the same time, through the refractive index difference between the core and the shell, the vividness and brightness of the photonic crystal structural color are guaranteed; in addition, the introduction of carbon black can effectively absorb the stray light generated in the self-assembly process of the crystal structural film, so as to improve the color rendering effect of the obtained structural film.

[0024] The modified polyurethane precursor liquid of the present invention contains hydroxyl groups on the main molecular chain. When cast on an opal photonic crystal template, the modified polyurethane precursor liquid can be combined with an ester group in the opal photonic crystal structure through hydrogen bonds, so that the modified polyurethane precursor liquid is uniformly dispersed in the array of the opal photonic crystals and firmly combined with the opal photonic crystals, thereby improving the compatibility of the modified polyurethane precursor liquid with the opal photonic crystals. At the same time, the modified polyurethane precursor liquid contains branched carboxyl groups. When combined with fabrics, the carboxyl groups can react with functional groups on fabric fibers to generate a cured product with a cross-linked structure, thereby improving color fastness. On the other hand, the hydrogen bonding forces between and within the molecules of the modified polyurethane precursor liquid can be enhanced, so that the chain segments between the molecules of the modified polyurethane precursor liquid are more tightly entangled, thereby improving the mechanical properties of the modified polycarbonate, thereby improving the elasticity and toughness of the structural color film, and when subjected to external forces, the modified polyurethane precursor liquid can synergistically act with modified nano-colloid microspheres to disperse stress, prevent the generation of cracks, and keep the photonic crystal structure from being destroyed, thereby improving the color fastness and durability of the structural color film. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] This embodiment provides a modified nanosphere, which is prepared by the following steps:

[0028] A1. Add 0.05 g of sodium dodecyl sulfate to 90 mL of deionized water, stir and mix, add 4 mL of styrene and 0.1 mL of divinylbenzene at 70 ° C, stir and react for 20 min, then add 15 mL of 2 wt% potassium persulfate solution, stir and mix, then dropwise add 11 mL of styrene and 0.4 mL of divinylbenzene, control the dropping time to 30 min, after the dropwise addition is completed, stir and react for 1 h, and then after rotary evaporation, obtain polystyrene colloidal microspheres;

[0029] A2. Add 8 mL of polystyrene colloid microspheres to 100 mL of deionized water, stir to mix, add 6 mL of methyl methacrylate and 10 mL of butyl acrylate dropwise, mix, and then add 0.2 mL of allyl methacrylate dropwise. The addition time is controlled to be 30 min. After the addition is completed, continue to stir the reaction for 1 h, and then after rotary evaporation, obtain modified nano-colloidal microspheres.

[0030] Example 2

[0031] This embodiment provides a modified nanosphere, which is prepared by the following steps:

[0032] A1. Add 0.08 g of sodium dodecyl sulfate to 90 mL of deionized water, stir and mix, add 4.5 mL of styrene and 0.15 mL of divinylbenzene at 75 ° C, stir and react for 25 min, then add 16 mL of 2 wt% potassium persulfate solution, stir and mix, then dropwise add 14 mL of styrene and 0.6 mL of divinylbenzene, control the dropping time to 35 min, after the dropwise addition is completed, stir and react for 1.2 h, and then after rotary evaporation, obtain polystyrene colloidal microspheres;

[0033] A2. Add 9 mL of polystyrene colloid microspheres to 100 mL of deionized water, stir to mix, add 7 mL of methyl methacrylate and 13 mL of butyl acrylate dropwise, mix, and then add 0.4 mL of allyl methacrylate dropwise. The addition time is controlled to be 35 min. After the addition is completed, continue to stir the reaction for 1.5 h, and then after rotary evaporation, obtain modified nano-colloidal microspheres.

[0034] Example 3

[0035] This embodiment provides a modified nanosphere, which is prepared by the following steps:

[0036] A1. Add 0.1 g of sodium dodecyl sulfate to 90 mL of deionized water, stir and mix, add 5 mL of styrene and 0.2 mL of divinylbenzene at 80 ° C, stir and react for 30 min, then add 18 mL of 2 wt% potassium persulfate solution, stir and mix, then dropwise add 15 mL of styrene and 0.8 mL of divinylbenzene, control the dropping time to 40 min, after the dropwise addition is completed, stir and react for 1.5 h, and then after rotary evaporation, obtain polystyrene colloidal microspheres;

[0037] A2. Add 10 mL of polystyrene colloid microspheres to 100 mL of deionized water, stir to mix, add 8 mL of methyl methacrylate and 15 mL of butyl acrylate dropwise, mix, and then add 0.5 mL of allyl methacrylate dropwise. The addition time is controlled to be 40 min. After the addition is completed, continue to stir and react for 2 h, and then obtain modified nano-colloidal microspheres after rotary evaporation.

[0038] Example 4

[0039] This embodiment provides a modified polyurethane precursor solution, which is prepared by the following steps:

[0040] To 15 g of polycarbonate diol, 0.1 mL of propylene glycol and 0.2 g of 2,2-dihydroxymethylbutyric acid were added, the mixture was stirred and mixed at 80 ° C, the temperature was lowered to 60 ° C, 1.5 mL of 4,4'-dicyclohexylmethane diisocyanate was added, the mixture was stirred and mixed, the temperature was lowered to 50 ° C, 0.3 mL of dibutyltin dilaurate was added, and the mixture was stirred and reacted for 2 min to obtain a modified polyurethane precursor solution.

[0041] Example 5

[0042] This embodiment provides a modified polyurethane precursor solution, which is prepared by the following steps:

[0043] To 18 g of polycarbonate diol, 0.3 mL of propylene glycol and 0.3 g of 2,2-dihydroxymethylbutyric acid were added, the mixture was stirred and mixed at 85 ° C, the temperature was lowered to 65 ° C, 2 mL of 4,4'-dicyclohexylmethane diisocyanate was added, the mixture was stirred and mixed, the temperature was lowered to 53 ° C, 0.4 mL of dibutyltin dilaurate was added, and the mixture was stirred and reacted for 3 minutes to obtain a modified polyurethane precursor solution.

[0044] Example 6

[0045] This embodiment provides a modified polyurethane precursor solution, which is prepared by the following steps:

[0046] To 20 g of polycarbonate diol, 0.5 mL of propylene glycol and 0.4 g of 2,2-dihydroxymethylbutyric acid were added, the mixture was stirred and mixed at 90 ° C, the temperature was lowered to 70 ° C, 3 mL of 4,4'-dicyclohexylmethane diisocyanate was added, the mixture was stirred and mixed, the temperature was lowered to 55 ° C, 0.5 mL of dibutyltin dilaurate was added, and the mixture was stirred and reacted for 5 minutes to obtain a modified polyurethane precursor solution.

[0047] Example 7

[0048] This embodiment provides a high color fastness structural color film, comprising the following steps:

[0049] S1, adding 80 parts by weight of modified nano-colloidal microspheres and 4 parts by weight of carbon black to 300 parts by weight of anhydrous ethanol, and ultrasonically dispersing for 40 minutes to obtain a microsphere dispersion;

[0050] S2, spreading the microsphere dispersion evenly on a smooth and flat polytetrafluoroethylene plate, and drying at 40° C. to obtain a modified microsphere opal photonic crystal template;

[0051] S3. Inject the modified polyurethane precursor liquid into the modified microsphere opal photonic crystal template, and then defoam under vacuum and solidify at 80° C. to obtain a high color fastness structural film with a thickness of 0.1 mm.

[0052] Example 8

[0053] This embodiment provides a high color fastness structural color film, comprising the following steps:

[0054] S1, adding 85 parts by weight of modified nano-colloidal microspheres and 5 parts by weight of carbon black to 350 parts by weight of anhydrous ethanol, and ultrasonically dispersing for 40 minutes to obtain a microsphere dispersion;

[0055] S2, spreading the microsphere dispersion evenly on a smooth and flat polytetrafluoroethylene plate, and drying at 43° C. to obtain a modified microsphere opal photonic crystal template;

[0056] S3. Inject the modified polyurethane precursor liquid into the modified microsphere opal photonic crystal template, and then defoam under vacuum and solidify at 80° C. to obtain a high color fastness structural film with a thickness of 0.3 mm.

[0057] Example 9

[0058] This embodiment provides a high color fastness structural color film, comprising the following steps:

[0059] S1, adding 90 parts by weight of modified nano-colloidal microspheres and 6 parts by weight of carbon black to 400 parts by weight of anhydrous ethanol, and ultrasonically dispersing for 40 minutes to obtain a microsphere dispersion;

[0060] S2, evenly spreading the microsphere dispersion on a smooth and flat polytetrafluoroethylene plate, and drying at 45° C. to obtain a modified microsphere opal photonic crystal template;

[0061] S3. Inject the modified polyurethane precursor liquid into the modified microsphere opal photonic crystal template, and then defoam under vacuum and solidify at 80° C. to obtain a high color fastness structural film with a thickness of 0.5 mm.

[0062] Comparative Example 1: Compared with Example 7, the modified nano-colloidal microspheres were replaced with silicon dioxide in equal amounts, and the rest were the same.

[0063] Comparative Example 2: Compared with Example 7, an equal amount of the modified polyurethane precursor liquid was replaced by the polyurethane precursor liquid, and the rest was the same.

[0064] Comparative Example 3: Compared with Example 7, no carbon black was added, and the rest was the same.

[0065] Performance tests were performed on Examples 7 to 9 and Comparative Examples 1 to 3. Mechanical performance test: referring to GB / T13022-1991, the stress of the film was tested. Optical performance test: the film was made into a 20 mm × 4 mm sample, and the color change was observed to be continuous and uniform during the stretching process from 0% to 50% strain. Reflection spectrum test: a stress of 3 MPa was applied to the surface of the structural color film, and a fiber optic spectrometer was used to test the reflectivity before and after the stress at a wavelength of 500 nm. The structure is shown in Table 1:

[0066] Table 1

[0067]

[0068] It can be seen from Table 1 that the stress of the structural color films prepared from modified polyurethane precursor liquid and modified nano-colloidal microspheres in Examples 7-9 is greater than that in Comparative Examples 1-3, and they have good mechanical stability, which improves the color fastness of the structural color films. At the same time, the color of the structural color films can change evenly and continuously during the stretching process, and they have good optical properties. The light reflectivity before and after being subjected to force is greater than that of Comparative Examples 1-3. In addition, compared with Comparative Examples 1-2, the change in reflectivity of the structural color film prepared in Example 7 after being subjected to stress is significantly lower than that of Comparative Examples 1-3, indicating that under the synergistic effect of the modified polyurethane precursor liquid and the modified nano-colloidal microspheres, the structural color film has better creep resistance and higher color fastness.

[0069] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0070] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a structural color film with high color fastness, It is characterized in that The following steps are involved: S1, adding modified nano-colloidal microspheres and carbon black into anhydrous ethanol, and ultrasonically dispersing for 40 minutes to obtain a microsphere dispersion; S2, evenly spreading the microsphere dispersion on a smooth and flat polytetrafluoroethylene plate, and drying at 40-45° C. to obtain a modified microsphere opal photonic crystal template; S3. Injecting the modified polyurethane precursor liquid into the modified microsphere opal photonic crystal template, and then vacuuming and defoaming, and curing at 80° C. to obtain a high color fastness structural film.

2. The method for preparing a structural color film with high color fastness according to claim 1, It is characterized in that The weight ratio of the anhydrous ethanol, the modified nano-colloid microspheres and the carbon black is 300-400:80-90:4-6.

3. The method for preparing a structural color film with high color fastness according to claim 1, It is characterized in that The thickness of the high color fastness structural film is 0.1-0.5 mm.

4. The method for preparing a structural color film with high color fastness according to claim 1, It is characterized in that The modified nano-colloidal microspheres are prepared by the following steps: A1. Add sodium dodecyl sulfate to deionized water, stir and mix, add styrene in a total amount of 25%-27% and divinylbenzene in a total amount of 7%-20% at 70-80°C, stir and react for 20-30 minutes, then add a 2wt% potassium persulfate solution, stir and mix, then dropwise add the remaining styrene and the remaining divinylbenzene, control the dropping time to 30-40 minutes, after the dropwise addition is completed, stir and react for 1-1.5 hours, and then after rotary evaporation, obtain polystyrene colloidal microspheres; A2. Add polystyrene colloidal microspheres to deionized water, stir to mix, add methyl methacrylate and butyl acrylate dropwise, mix, and then add allyl methacrylate dropwise. Control the addition time to be 30-40 min. After the addition is completed, continue to stir the reaction for 1-2 h, and then obtain modified nano-colloidal microspheres after rotary evaporation.

5. The method for preparing a structural color film with high color fastness according to claim 4, It is characterized in that The usage ratio of the deionized water, sodium dodecyl sulfonate, styrene, divinylbenzene and potassium persulfate solution is 90 mL: 0.05-0.1 g: 15-20 mL: 0.5-1 mL: 15-18 mL.

6. The method for preparing a structural color film with high color fastness according to claim 4, It is characterized in that The volume ratio of the deionized water, the polystyrene colloidal microspheres, the methyl methacrylate, the butyl acrylate and the allyl methacrylate is 50:4-5:3-4:5-7.5:0.1-0.

25.

7. The method for preparing a structural color film with high color fastness according to claim 4, It is characterized in that The particle size of the modified nano-colloid microspheres is 200-300nm.

8. The method for preparing a structural color film with high color fastness according to claim 1, It is characterized in that The modified polyurethane precursor solution is prepared by the following steps: Add propylene glycol and 2,2-dihydroxymethylbutyric acid to polycarbonate diol, stir and mix at 80-90° C., cool to 60-70° C., add 4,4'-dicyclohexylmethane diisocyanate, stir and mix, cool to 50-55° C., add dibutyltin dilaurate, stir and react for 2-5 minutes to obtain a modified polyurethane precursor solution.

9. The method for preparing a structural color film with high color fastness according to claim 8, It is characterized in that The usage ratio of the polycarbonate diol, propylene glycol, 2,2-dihydroxymethylbutyric acid, 4,4'-dicyclohexylmethane diisocyanate and dibutyltin dilaurate is 15-20 g: 0.1-0.5 mL: 0.2-0.4 g: 1.5-3 mL: 0.3-0.5 mL.

10. A structural color film with high color fastness, It is characterized in that Prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Structural color coating based on photonic crystal microspheres as well as preparation method and application of structural color coating

    CN121950159A